STRATEGI PENGEMBANGAN POTENSI OLAHRAGA REKREASI DI OBJEK WISATA DANAU TALANG KECEMATAN DANAU KEMBAR KABUPATEN SOLOK - M Rendy Nuryadin; Donal Syafrianto; nuridin widya pranoto; Ahmad Chaeroni; Iit Selviani (Jurnal IKEOR, 2023)
The issue that the specialists found was that the Talang Lake vacation spot had not yet fostered the possible for good sporting games, particularly offices that could be utilized by guests, framework offices were all the while lacking, hence creating procedures for good sporting sports was important. This study plans to decide the methodology for fostering the capability of sporting games in the Lake Talang vacation destination, Twin Lakes Area, Solok Rule. This sort of examination is utilized is enlightening subjective, specifically an investigation used to depict or tackle issues deliberately utilizing the SWOT examination technique, in particular the examination expected to see the degree to which the methodology of creating vacation spots is executed in expanding sightseers in light of qualities, shortcomings, open doors, and dangers. The chance for Lake Talang to turn into a tasteful the travel industry potential in the event that it is coordinated and overseen appropriately from the get-go. This lake will be an option for family sports diversion for the neighborhood local area or an objective of decision for homegrown sightseers. The methodology took on by the administration is the place of endlessly keep up with. This condition is the key in deciding potential techniques that can be created concerning market entrance and item improvement as per the administration's circumstances. The subsequent four primary techniques are holding socialization of Sapta Pesona or consciousness of the advantages of the travel industry for all degrees of society in a manageable and deliberate way, creating local area based the travel industry, the travel industry should have the travel industry confirmation and holding setting up camp celebrations to going bikes.